2020
DOI: 10.1186/s12889-020-09729-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based strategy for prevention of hidden hunger among adolescents in a suburb of Nigeria

Abstract: Background Hidden hunger (micronutrient deficiencies) among adolescents are linked to impaired physical growth, poor cognitive function, low resistance to infection as well as degenerative and chronic diseases at later age. To prevent these deleterious impacts of hidden hunger, effective intervention strategy that improves nutrition knowledge and promotes healthy food choices among this age-group becomes imperative. The intervention was to evaluate the impact of a 14-page locally developed nutrition education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Following the educational intervention, a remarkable increase in knowledge was noted. This is in accordance with interventional studies carried out in Nigeria, 11 ,India, 12 and Tehran, 13 which show that educational interventions carry a significant effect on nutrition knowledge and practices among adolescents. In comparison to the study conducted in Hyderabad, India, 12 in which two modes of intervention were used, our study only used multimedia presentation as the main intervention strategy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Following the educational intervention, a remarkable increase in knowledge was noted. This is in accordance with interventional studies carried out in Nigeria, 11 ,India, 12 and Tehran, 13 which show that educational interventions carry a significant effect on nutrition knowledge and practices among adolescents. In comparison to the study conducted in Hyderabad, India, 12 in which two modes of intervention were used, our study only used multimedia presentation as the main intervention strategy.…”
Section: Discussionsupporting
confidence: 90%
“…Pre-test was taken to assess their baseline knowledge about micronutrients using an intervieweradministered, validated, closed ended questionnaire. 11 The questionnaire consisted of three parts. Part A was based on sociodemographic details and eating habits of participants.…”
Section: Methodsmentioning
confidence: 99%
“…Alongside micronutrient deficiency or hidden hunger, inadequate dietary intake of necessary minerals and vitamins has also imparted severe effects on human health. Currently, approximately two billion population worldwide is affected by micronutrient deficiency or hidden hunger (White and Broadley 2011 ; Ritchie et al 2018 ; Ibeanu et al 2020 ) and the impacts are more prominent in the African continent and South Asian countries. In these regions, the infants and particularly women at the reproductive stage are mostly affected by malnourishment, lacking sufficient dietary minerals and vitamins, leading to severe growth problems and various birth related issues.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…[11,12] Studies have shown that most adolescents need more knowledge about their health, development, and nutritional needs. [13][14][15] Therefore, ensuring good adolescent dietary habits is crucial as a nutrient-poor diet predisposes to poor physical and cognitive development. [16,17] Dietary diversification is one of the globally recognised strategies for addressing the problem of malnutrition, particularly micronutrient malnutrition.…”
Section: 2023________________________280mentioning
confidence: 99%